Synthesis and Biological Activity of 2,7-Naphthyridine Derivatives: An Overview - Wójcicka, Anna (Current Organic Chemistry, 2021)
2,7-Naphthyridine is one of the six structural isomers of pyridopyridine. Biological investigations have shown that these compounds have a broad spectrum of activity. They have been found to have antitumor, antimicrobial, analgesic and anticonvulsant effects. The broad spectrum of biological activity of 2,7-naphthyridine derivatives is the main reason for the preparation of new compounds containing this scaffold. This review aims to present various methods of obtaining 2,7-naphthyridine analogs. Compounds containing a 2,7-naphthyridine moiety can be synthesized from a variety of substrates and may be classified into four main categories: those derived from acyclic compounds, from quinoline derivatives, from pyridine derivatives, and from other compounds. Most of them were obtained by the cyclocondensation or intramolecular cyclization of pyridine derivatives. Cyclocondensations of non-cyclic substrates also produced 2,7-naphthyridine derivatives. Tricyclic benzo[2,7]naphthyridines were prepared from quinolines. The 2,7-naphthyridine scaffold has also been synthesized by the rearrangement of pyrrolo[3,4-c]pyridines, pyrano[3,4-c]pyridines or thiopyrano[3,4-c]pyridines.
Keywords: pyridopyridines